Analysis of Parking Space Needs on the Kornita High School - Syaiful, Syaiful; Rulhendri, Rulhendri; Murtejo, Tedy; Saputra, Alvian Aditya; Wardhani, Asri Kusuma; Ngadimo, Ngadimo (ASTONJADRO, 2026)
Kornita High School is a Senior High School located on Jalan Tanjung Kampus IPB Darmaga Bogor, which is under the auspices of the Dharma Foundation of the Bogor Agricultural Institute. The school has grown and developed since 1986. Generally, in the school area, the need for parking space is quite large considering that most students, teachers, and employees bring private vehicles. In solving this problem, this study aims to determine the characteristics of parking, capacity and parking space needs that occur at this time. Based on the data obtained from the maximum volume of motorcycle parking included in the parking load, namely the number of vehicles during a certain time period occurred on Monday, October 23, 2023, as many as 149 vehicles, with the maximum accumulation of motorcycle parking vehicles parked during a certain time period of 148 vehicles, with a maximum motorcycle parking duration (in hours) of 10:00 hours. For the maximum average duration, it occurred at 09:36 hours. For the minimum duration, it occurred at 0:47 minutes, with the highest parking turn over of motorcycles in a certain period of time reaching 123.14%. The motorcycle parking index is the percentage of the number of vehicles parked in the Kornita High School parking area, the highest reaching 122.31%, this shows that the performance of motorcycle parking is quite high, this is indicated by seeing the parking index exceeding 100%. thus the parking capacity for motorcycles available is not sufficient to accommodate motorcycles in the Kornita High School parking lot.